Pharmacological characterization of tachykinin tetrabranched derivatives. (September 2014) - Ruzza, Chiara; Rizzi, Anna; Malfacini, Davide; Cerlesi, Maria Camilla; Ferrari, Federica; Marzola, Erika; Ambrosio, Caterina; Gro, Cristina; Severo, Salvadori; Costa, Tommaso; Calo, Girolamo; Guerrini, Remo
<x xml:space="preserve">Abstract</x> Background and Purpose Peptide welding technology (PWT) is a novel chemical strategy that allows the synthesis of multibranched peptides with high yield, purity and reproducibility. Using this technique, we have synthesized and pharmacologically characterized the tetrabranched derivatives of the tachykinins, substance P (SP), neurokinin A (NKA) and B (NKB). Experimental Approach The following in vitro assays were used: calcium mobilization in cells expressing human recombinant NK receptors, BRET studies of G‐protein – NK1 receptor interaction, guinea pig ileum and rat urinary bladder bioassays. Nociceptive behavioural response experiments were performed in mice following intrathecal injection of PWT2‐SP. Key Results In calcium mobilization studies, PWT tachykinin derivatives behaved as full agonists at NK receptors with a selectivity profile similar to that of the natural peptides. NK receptor antagonists display similar potency values when tested against PWT2 derivatives and natural peptides. In BRET and bioassay experiments PWT2‐SP mimicked the effects of SP with similar potency, maximal effects and sensitivity to aprepitant. After intrathecal administration in mice, PWT2‐SP mimicked the nociceptive effects of SP, but with higher potency and a longer‐lasting action. Aprepitant counteracted the effects of PWT2‐SP in vivo. Conclusions and Implications The present study has shown that the PWT technology can be successfully applied to the peptide sequence of tachykinins to generate tetrabranched derivatives characterized with a pharmacological profile similar to the native peptides. In vivo, PWT2‐SP displayed higher potency and a marked prolongation of action, compared with SP.